Risk of contamination of Arsenic in groundwater mapping along the Mekong River in 5 provinces of Laos: https://doi.org/10.69692/SUJMRD0901364 - Vongphouthone, Banthasith; Pongpanya, Phanthoudeth; Phonhalath, Keophousone; Keokangdong, Sengphet; Manivong, Thipphamala; Soysouvanh, Vongsavanh; Visaiphone, Soulisack (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Arsenic (As) contamination of groundwater is often caused by As leaching from geological formations. This study focused on As concentration and illustrated risk of As concentration in groundwater of 5 provinces along the Mekong River, Laos. The study area is Bolikhamxay Province, Khammouane Province, Savannakhet Province, Salavan Province and Champasak Province. The average concentration of arsenic in groundwater is ranged 1-10 µg/l, which is within the Laos national environmental standard. However, some areas had high concentration in Khongsedone District, Pathouphone District, Soukhoumma District, and Champassack District (15-30 µg/l) which is a flat area and low land of the Mekong River flows. The Geographic Information System (GIS) program predicted a risk map of arsenic in groundwater, it can be a preliminary map in future research and sources tracking of arsenic.